The genus Crenitulus in Venezuela (Hydrophilidae: Chaetarthriinae: Anacaenini) with description of twelve new species (UNED Research Journal, 2018)
Beetles of the genus Crenitulus have been reported for the Neotropical region and Australia. In Venezuela this genus was completely unknown, and I record it for the first time in this investigation. I describe twelve new species of the family Hydrophilidae belonging to the genus Crenitulus in Venezuela. It was registered for the first time in Venezuela with: C. amazonenses sp. nov., C. camachoi sp. nov., C. cherylae sp. nov., C. diferentis sp. nov., C. gamboa sp. nov., C. maluz sp. nov., C. marialuisae sp. nov., C. megnai sp. nov., C. nayariyaleskiae sp. nov., C. negrus sp. nov., C. perijanus sp. nov., C. venezuelensis sp. nov., and C. suturalis, collected in three microhabitats: hygropetric, madi and ramentum. The habitus, genital organs, thoracic and cephalic appendices are illustrated. A key to identify the species and a map for the geographical location of the species in Venezuela is presented.
Keywords: aquatic insect; Coleoptera; Neotropical region; system hydrobiology; water scavenger beetles